Job Satisfaction among Health Workforce in Medical Colleges of Nepal: A Mixed Method - Dahal, Dipak Prasad; Gupta, Nidhi (Journal of Nepal Health Research Council, 2025)
Background: The medical sector in the society and its significant role of job satisfaction will improve the health workforce performance. Presently staffs/workforce management in medical colleges became more challenges. The purpose of the study was to investigate the level of job satisfaction and associated factors in medical colleges of Nepal. Methods: The study employed descriptive, cross-sectional study with the relevant respondents’ such as doctors, nurses and administrative staffs working in different medical colleges of Nepal. The study was conducted within the affiliated college of Kathmandu University School of Medical Sciences (KUSMS). Simple random sampling method was used to select respondents. A total sample size of 108 for quantitative and 18 for qualitative was collected, using the formula from Charan and Biswas, 2013. For qualitative study, we used purposive convenience sampling strategy to enroll the health workers for key informant interview to gather data on job satisfaction, impression and experience about their job. Results: 34.3% of the respondents, we surveyed were not satisfied with their job while 65.7% were satisfied with their current job. It has also been discovered that the delivery of high-quality health care depends on the level of job satisfaction with the healthcare organization. Conclusions: There was a significant relationship between job satisfaction of health workforce and its’ associated factors in medical college of Nepal. A focus on improving work environment through increased financial motivation and career development opportunities as well as investing in health insurance for diseases with increased resources support is recommended to improve job satisfaction. Keywords: Associated factors; health workforce; job satisfaction; medical college.